If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -2g = 4(4 + g) + 2g + -4(6 + -3g) -2g = (4 * 4 + g * 4) + 2g + -4(6 + -3g) -2g = (16 + 4g) + 2g + -4(6 + -3g) -2g = 16 + 4g + 2g + (6 * -4 + -3g * -4) -2g = 16 + 4g + 2g + (-24 + 12g) Reorder the terms: -2g = 16 + -24 + 4g + 2g + 12g Combine like terms: 16 + -24 = -8 -2g = -8 + 4g + 2g + 12g Combine like terms: 4g + 2g = 6g -2g = -8 + 6g + 12g Combine like terms: 6g + 12g = 18g -2g = -8 + 18g Solving -2g = -8 + 18g Solving for variable 'g'. Move all terms containing g to the left, all other terms to the right. Add '-18g' to each side of the equation. -2g + -18g = -8 + 18g + -18g Combine like terms: -2g + -18g = -20g -20g = -8 + 18g + -18g Combine like terms: 18g + -18g = 0 -20g = -8 + 0 -20g = -8 Divide each side by '-20'. g = 0.4 Simplifying g = 0.4
| 3/8(4p+6)=1/2p-17 | | -6.5v-7+5v=-27.5 | | 9x-5(x-6)=10 | | 3x+2=-2xn-8 | | n-19=48 | | (y*2)+15=55 | | -2/5(45) | | x+0.75=14 | | 55=15+(y*2) | | 8-12-(-6)= | | x^2-21x+25=0 | | 7+4(1-6.5s)=21.5 | | (y*2)+15= | | 7s-25=-23+8s | | 4r-6=9+r | | 6.5x+20=(10+x)(4) | | n-4=43 | | 3b-2(b-5)=2(b+4) | | 280=53l | | (55-15)/2= | | 9x+4=8x+14 | | -2(4+-7k)+9=-13 | | 7626=93w | | 8/5x-3=2 | | 9x+14=9x+4 | | -15=1-5x-3x | | 9x+15=2-3x | | (7x-5)+(6x-5)+(9x-11)=180 | | 22.5+7(n-3.4)=22.5+7(n-3.4) | | z=ax+by+cxy | | 12h-(9h-5)=17 | | 4x-4+x=51 |